The Implementation of Problem-Based Learning Model to Enhance Students' Understanding of National Identity Material in Secondary Schools - Sandra Dwi Hidayani (PT. Mifandi Mandiri Digital, 2024)
This Classroom Action Research (CAR) aims to address learning challenges faced by students, particularly in Civic Education (PPKn), which is often perceived as a tedious subject. Professional teachers are expected to apply various instructional models and media to enhance the quality of learning. The primary objective of this study is to evaluate the effectiveness of implementing the Problem-Based Learning (PBL) model in improving students' learning outcomes in Civic Education while simultaneously fostering national identity through the integration of local historical values. This qualitative study collected data through observation, interviews, documentation, literacy review, and testing. The research subjects were 15 eighth-grade students of MTs Al-Hidayah Patumbak for the academic year 2022/2023, with the Civic Education teacher acting as the practitioner, peers serving as learning process observers, and the principal as an additional data source. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The findings revealed that the implementation of the Problem-Based Learning model effectively enhanced students' motivation and academic achievement in Civic Education. Moreover, the use of local history-based instruction successfully cultivated a sense of unity and strengthened students' national identity, confirming that Classroom Action Research utilizing the PBL model provides a concrete solution for addressing learning difficulties in Civic Education.